Socio-Demographic Correlates of Health and Nutrition Among Rural and Plantation Communities of the western Dooars, Jalpaiguri district, West Bengal, India - Souraditya Chakraborty; Ayush Kumar Sah; Ayushman Pradhan; Keshab Sharma; Lalita Agarwal; Laxmi Pradhan; Mamta Sahu; Mausumi Roy; Monisha Khanam; Nabin Paul (Journal of Food Innovation, Nutrition, and Environmental Sciences, 2025)
Health and nutrition outcomes are profoundly influenced by socio-demographic factors, particularly in economically and geographically marginalized communities. This study investigated the health and nutritional status of tea garden workers and forest fringe village residents in selected areas of the western Dooars region of Jalpaiguri district, West Bengal, India. The primary objectives were to assess the demographic and socio-economic profiles of the population, explore correlations between socio-demographic variables and nutritional status, and suggest recommendations for betterment of community well-being. A community-based cross-sectional study was done from September 2024 to January 2025. Data were collected from 156 adult participants (101 males, 55 females) using a pre-structured questionnaire through a multi-stage random sampling technique. Variables analysed included age, gender, occupation, income, education. Results revealed substantial disparities in age, gender, occupation, income, education, addiction status, food security. Undernutrition, poor dietary diversity, and limited access to healthcare was prevalent, especially among female and elderly respondents. The findings highlighted the urgent need for targeted policy interventions focusing on nutrition education, healthcare accessibility, and livelihood support. Strengthening community-based initiatives and implementing development programs tailored to the unique needs of these vulnerable populations are essential for promoting equitable and sustainable health outcomes in the region.